Academia at a critical point: David Lodge’s Small World - Wojciech Nowicki (Facta Simonidis)
The article discusses Small World, one of the most popular campus novels by the contemporary author David Lodge. What distinguishes Small World is the theme of academia: nearly all major characters are lecturers in literature. Lodge involves the reader in an intertextual game whose meanings are available only to experts, i.e. lecturers themselves, since most readers may overlook the fact that the novel is a satirical remake of Arthurian romance. The “critical point” mentioned in the title of the article alludes to critical debates in the novel, to a critique of the academic institution as such and indicates Small World as the climax of the genre.